(untitled) (Georgian Journal for European Studies, 2017)
Implementing Innovative Teaching Methods in European Union Law Modules This article illustrates the innovative teaching methods implemented by Professor Natia Lapiashvili in the European Union Law modules at the Institute for the European Studies at Tbilisi State University. The article analyses the combination of the traditional classroom teaching with the Problem-Based Learning (PBL), E-Learning and Simulation exercises. For PBL, after explaining its concept, some frequently raised questions during her classes are presented to demonstrate the application of this method. In the context of e-learning, the article evaluates the usefulness of having pre-recorded video lectures for each topic, which facilitates the flexibility of the learning process and aids self-discipline of the students. The simulation exercises also proved to be very effective at all European Union Law modules, as the students show particular enthusiasm and engagement during discussions. The paper argues that the described innovative teaching methods increase students’ comprehension of various legal issues by putting them in a real-life context. The focus on students’ individual needs and interests facilitates life-long learning and results in improved academic achievements, which must be the primary objective for any modern educational system.